Structural, Spectroscopic and Biological Aspects of O, N- Donor Schiff Base Ligand and its Cr(III), Co(II), Ni(II) and Cu(II) Complexes Synthesized through Green Chemical Approach - Kavita Rathore; Rajiv K. R. Singh; H. B. Singh (E-Journal of Chemistry)
The monofunctional bidentate Schiff base ligand (o-vanillin) p-chloroaniline and its four new complexes of chromium(III), cobalt(II), nickel(II) and copper(II) have been synthesized by classical thermal and microwave-irradiated techniques. All the new derivatives have been characterized by elemental analysis, molecular weight determinations, molar conductance measurements, UV-Vis, IR and NMR spectral studies. The IR spectral data suggest the involvement of phenolic oxygen after deprotonation and azomethine nitrogen in coordination to the central metal ion. The growth inhibiting potential of the ligands and complexes has been assessed against a variety of fungal and bacterial strains.